2021
DOI: 10.1186/s12913-021-06729-1
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with response and remission from depression at 6-months of treatment in a retrospective cohort treated within an integrated care program

Abstract: Background Depression causes significant morbidity, which impacts mental health, overall general health outcomes, everyday functioning and quality of life. This study aims to contribute to knowledge in the field through enhanced understanding of factors that influence depression response and remission, with consideration for design of treatment services to optimize depression outcomes within integrated care programs. Methods Using routine behaviora… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Yu et al (59) showed that cognitive decline and mobility problems in older adults predicted emergency department visits and that mobility problems predicted poorer quality of life. In addition, depression in older adults can lead to significant morbidity, which can affect physical and mental health, overall health outcomes, daily functioning and quality of life (60). However, only five studies (25, [38][39][40]48) recruited psychologists to form multidisciplinary teams and did not specifically provide care services for psychological problems in older adults, instead recommending comprehensive initial assessment using standardized rating scales, follow-up monitoring, the provision of care manager-led psychological support techniques (61,62), and the development of goal plans to improve physical and mental health and mobility-related health problems.…”
Section: Discussionmentioning
confidence: 99%
“…Yu et al (59) showed that cognitive decline and mobility problems in older adults predicted emergency department visits and that mobility problems predicted poorer quality of life. In addition, depression in older adults can lead to significant morbidity, which can affect physical and mental health, overall health outcomes, daily functioning and quality of life (60). However, only five studies (25, [38][39][40]48) recruited psychologists to form multidisciplinary teams and did not specifically provide care services for psychological problems in older adults, instead recommending comprehensive initial assessment using standardized rating scales, follow-up monitoring, the provision of care manager-led psychological support techniques (61,62), and the development of goal plans to improve physical and mental health and mobility-related health problems.…”
Section: Discussionmentioning
confidence: 99%
“…2023; Jeffrey et al, 2021). This negative relationship between ACEs and mental health remains even after accounting for social determinants of health such as socioeconomic status (Wooldridge et al, 2023).…”
mentioning
confidence: 99%
“…Furthermore, depression experienced by ACE survivors differs from those who have not experienced abuse. ACEs are associated with more episodes of depression, greater chronicity, and less symptom reduction in response to treatment (Giampetruzzi et al, 2023; Jeffrey et al, 2021). This negative relationship between ACEs and mental health remains even after accounting for social determinants of health such as socioeconomic status (Wooldridge et al, 2023).…”
mentioning
confidence: 99%